DESIGN AND DEVELOPMENT OF UNDERWATER ROBOT FOR CLEANING PROCESS - Mohd Aras, Mohd Shahrieel (Journal of Advanced Manufacturing Technology (JAMT), 2016)
Underwater vehicles are a type of vehicle that a type of vehicles that able to explore the underwater world. Remotely Operated Crawler (ROC) is one of the Unmanned Underwater Vehicle (UUV) that can be categorized in Remotely Operated Vehicle (ROV) class. The specialty of ROC allows for underwater intervention by staying a direct contact with the seabed. The common issues face for the crawlers are the underwater pressure, maneuverability, power and control. Besides that, the surface of the seabed become one of the problems in that restrict on ROC maneuverability. Designing a ROC that can crawl in any surface conditions is one of the issues emerged in this project. This project is about developing the ROC in order to fulfil a specific mission involving certain tasks. ROC lend themselves to long-term work and offer a very stable platform for manipulating objects and taking measurements better than other ROV. Development the ROC based on wheel mechanism that allows the ROC moves with direct contact with the seabed without any glitch and have an ability to operate in any condition of the underwater environment. The wheel mechanism is adapted based on the tanks which is the chain type wheels. The performance of the ROC will be verified based on experiments conducted on the cluttered condition either on the surface or underwater. The operation of ROC can achieve excellent performance with an unexpected level of environmental condition.